2001
DOI: 10.1007/3-540-44647-8_28
|View full text |Cite
|
Sign up to set email alerts
|

New Public Key Cryptosystem Using Finite Non Abelian Groups

Abstract: Abstract. Most public key cryptosystems have been constructed based on abelian groups up to now. We propose a new public key cryptosystem built on finite non abelian groups in this paper. It is convertible to a scheme in which the encryption and decryption are much faster than other well-known public key cryptosystems, even without no message expansion. Furthermore a signature scheme can be easily derived from it, while it is difficult to find a signature scheme using a non abelian group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 16 publications
0
72
0
2
Order By: Relevance
“…In this section, generalizing the various ideas of [7,9,14], we show that it is possible to w-reduce(see the definition below) DLP(Inn(G)) to DLP(Inn(H)), where H is a maximal normal subgroup of G.…”
Section: Group Extensions and Mor Cryptosystemmentioning
confidence: 95%
See 4 more Smart Citations
“…In this section, generalizing the various ideas of [7,9,14], we show that it is possible to w-reduce(see the definition below) DLP(Inn(G)) to DLP(Inn(H)), where H is a maximal normal subgroup of G.…”
Section: Group Extensions and Mor Cryptosystemmentioning
confidence: 95%
“…In [7,9], it is shown that DLP over inner automorphism groups of semidirect products can be reduced to DLP over inner automorphism groups of individual groups. For group extensions, a similar result can be derived.…”
Section: Corollary 7 (Seementioning
confidence: 99%
See 3 more Smart Citations